Late‐Stage Functionalization and Characterization of Drugs by High‐Throughput Desorption Electrospray Ionization Mass Spectrometry. Issue 1 (5th January 2022) - Huang, Kai‐Hung; Ghosh, Jyotirmoy; Xu, Shiqing; Cooks, R. Graham
Abstract: Late‐stage functionalization (LSF) of drug molecules is an approach to generate modified molecules that retain functional groups present in the active drugs. Here, we report a study that seeks to characterize the potential value of high‐throughput desorption electrospray ionization mass spectrometry (HT DESI‐MS) for small‐scale rapid LSF. In conventional route screening, HT‐based DESI‐MS provides contactless, rapid analysis, reliable and reproducible data, minimal sample requirement, and exceptional tolerance to high salt concentrations. Ezetimibe (E), an established hypertension drug, is targeted for modification by LSF. C−H alkenylation and azo‐click reactions are utilized to explore this approach to synthesis and analytical characterization. The effect of choice of reactant, stoichiometry, catalyst, and solvent are studied for both reactions using high throughput DESI‐MS experiments. Optimum conditions for the formation of LSF products are established with identification by tandem mass spectrometry (MS/MS). Abstract : A high‐throughput‐based late‐stage functionalization using desorption electrospray ionization mass spectrometry (DESI‐MS) is reported in this work. Azo‐click (red) and C−H alkenylation (blue) reactions on Ezetimibe were investigated. Various reactants, solvents, stoichiometries, and catalysts were also investigated, and optimum conditions were decided in a high‐throughput manner. Subsequent structural confirmation was achieved in situ by tandem mass spectrometry.